KARAKTERISTIK FISIK DAN KIMIA GELATIN KULIT SAPI DENGAN JENIS DAN KONSENTRASI ASAM SEBAGAI LARUTAN PRE TREATMENT - Dwi Wulandari; R.L.M. Satrio Ari Wibowo; Tantri Fauziah; A. Z.Tawarniate (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2023)
The aim of the research was to study the physical and chemical properties of bovine skin gelatin soaked in different types and concentrations of acids and to obtain the types and concentrations of acids that could produce good quality gelatin. The materials used in the study were 10 kg of PO fresh cowhide, acetic acid, HCl and lime citric acid. The treatment applied was the percentage of acid, namely 3%, 4% and 5%. Parameters observed included yield, moisture content, ash content, pH, fat content, protein content, gel strength and viscosity. Statistical analysis was used with a completely randomized design with factorial pattern with 2 repetitions, as the first level is the type of acid, namely CH3COOH, HCL and C 6H8O7 and the second level is the percentage of acid: 3%, 4%, 5%. The data obtained were analyzed using ANOVA (Co Variance Analysis) based on a completely randomized factorial design. If there is a difference, proceed with Duncan's multiple area test. The interaction between the type of acid and the percentage of acid affects all parameters. Treatment with HCl gave the highest yield of 18.05% and the pH closest to normal was 4.62. Acetic acid treatment resulted in the highest protein content, gel strength and viscosity (95.94%, 222.01 Bloom, 10.44 cP). Treatment with lime citric acid obtained the lowest ash content of 0.36%.